Religion and civil society rethinking public religion in the contemporary world - Herbert, David (Ashgate religion, culture & society series, 2003)
This book presents the first full-length study of the relationship between religion and the controversial concept of civil society. Across the world in the last two decades of the twentieth century religions re-entered public space as influential discursive and symbolic systems apparently beyond the control of either traditional religious authorising institutions or states. This differentiation of religion from traditional institutions and entry into secular public spheres carries both dangers and possible benefits for democracy.